Techniques for Treating a Single Cold Thyroid Nodule - Arifullah, Azam Khan, Muhammad Hussain Afridi, Syed Zafar Hasan, Khaddija Bibi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The goal of this article is to raise awareness of malignancy and surgical options for the solitary inflection point of the cold nodule thyroid. Methods: People mentioned after the community or hospitalized straight via Observational Patient Treatment Tartary care hospital kpk with a diagnosis of a single cold nodule thyroid gland were accounted for in the study. Results: The patients' ages varied from 15 to 65, with a mean of 35 10 years, and 90% were female. Sixty-four percent of patients had problems in the right lobe of the thyroid gland, whereas only two percent had problems in the isthmus. Each patient had had surgery and was deemed euthyroid. In 50% of patients, FNAC revealed adenomatous colloid goiter, while in 5%, FNAC revealed papillary cancer of the thyroid gland. Mainly, lobectomy with isthmusectomy was done (95%), whereas complete thyroidectomy was done (5%). Adenomatous colloid goiter was found in 45% of patients, whereas 9% had thyroid cancer that forms in follicles, and 3% had cancer of the follicle based on the histopathology report. In 7% of those who needed it, complete thyroid removal was accomplished. Postoperatively, 5% of patients had an infection at the surgical site, and 3% experienced temporary hypocalcemia. People didn't die outright or anything like that. Conclusion: Women are more likely to have a single cold nodule in their thyroid gland. The most effective surgical procedure is a combination of lobectomy and isthmusectomy. When a single cold nodule develops in the thyroid, papillary carcinoma is the most prevalent kind of cancer that may develop there. Keywords: Techniques, Treating, Cold Thyroid, Nodule